Malolactic Fermentation: The ABC’s of MLF - Lerm, E.; Engelbrecht, L.; du Toit, M. (South African Journal of Enology and Viticulture, 2016)
There are two main fermentations associated with the winemaking process. Alcoholic fermentation is conducted by the yeast culture and malolactic fermentation takes place as a result of the metabolic activity of lactic acid bacteria, specifically from the genera Oenococcus, Lactobacillus, Pediococcus and Leuconostoc. Malolactic fermentation is defined as the conversion of malic acid to lactic acid and CO2 and besides deacidification also contributes to microbial stability and modification of the aroma profile. This paper aims to provide a comprehensive review discussing all the main aspects and factors related to malolactic fermentation, including practical considerations for monitoring and ensuring a successful fermentation.